Modelling of the early stage of retinal neurodegeneration via a topical injection of dopaminergic neurotoxin - T. A. Pavlenko; N. B. Chesnokova; O. V. Beznos; A. V. Grigoryev; T. D. Okhotsimskaya; N. N. Shikareva (Российский офтальмологический журнал)
Purpose: to develop a model of the early stage of retinal neurodegeneration via an intravitreal injection of the dopaminergic neurotoxin. Material and methods. The experiment was carried out on 20 Chinchilla rabbits. The experimental groups received intravitreal injection of 0.1 ml of 6-hydroxydopamine (6-OHDA) in NaCl 0.9 % with 0.5 % ascorbate, containing 0.25 or 0.5 mg 6-OHDA. The control group received injections of 0.1 ml of NaCl-ascorbate solution without neurotoxin. On the 7th and the 14th days after the injection, intraocular pressure (IOP), pupillary light reaction and ocular blood flow were estimated and the fundus was examined. On the 7th day after an injection of 0.25 mg 6-OHDA, we used ELISA to measure dopamine concentration in retinal homogenates, while on the 14th day after an injection of 0.5 mg 6-OHDA, the concentrations of dopamine, norepinephrine, TNF-a and endothelin-1 were measured by the same method. Results. On the 7th day after a 0,25 mg injection of neurotoxine, we revealed a decrease of dopamine in the retina (0.043 ± 0.130 pg/mg protein compared with 0.10 ± 0,03 pg/mg protein in the controls, р < 0.01). On the 14th day, dopamine and norepinephrine levels showed a fourfold increase (р < 0.05). An injection of 0.5 mg of 6-OHDA caused a threefold increase of dopamine (р < 0.05) and a fivefold increase of norepinephrine (р < 0.01) concentration in comparison with the controls. On the 14th day, endotheline-1 level was 65 % higher than in the controls after a 0.25 mg 6-OHDA injection (р < 0.01) and 45 % higher after a 0,5 mg injection (р<0.05). At the same time, TNF-α levels increased by 43 % (р < 0.05) and 20 % (р < 0.05) respectively. We also revealed a dose-dependent change of IOP, a disturbance of pupillary light reaction and decreased ocular blood flow after an injection of neurotoxin. Conclusion. A single intravitreal injection of dopaminergic neurotoxin 6-OHDA in the amount of 0.25 or 0.5 mg per eye leads to a neuroinflammation and vascular disorders, which are the main pathogenetic pathways of neurodegeneration. To model its early phase, the 0.25 mg dose is preferable as it causes less dramatic functional disorders. The latter model can be useful for the investigation of retinal neurodegeneration pathogenesis, the search for early diagnostic and prognostic markers thereof and the estimation of therapy effectiveness.